Sertifikat Sebagai Bukti Hak Kepemilikan Atas Tanah Perspektif Hukum Islam - Muhammad Akbar Herman; Hamzah Hasan; Saleh Ridwan (Danudirja Setyabudi Nusantara, 2025)
This study presents three research questions: First, what is the concept of proof of land ownership rights from the perspective of Islamic law? Second, what is the process of issuing land certificates as proof of land ownership rights according to Islamic law ? Third, what is the legal force of land certificates as proof of land ownership rights according to Islamic law? The type of research used is library research with a normative theological (sharia) approach. The data sources used are data obtained indirectly (secondary data), including primary sources such as the Qur'an, Hadith, and legislation; secondary sources like literature and scientific journals; and tertiary sources such as magazines, dictionaries, and Google. The results of this study show that: First, the concept of proof of land ownership in Islamic law aims to provide legal certainty regarding land ownership rights. Proof of land ownership can be in the form of written documents (kitabah), testimony (syahadah), and continuous physical control (qabdh wa istighlal). Second, applying Islamic legal principles such as justice (al-'adalah), benefit (al-maslahah), transparency (al-ṣidq), and public announcement (I'lan) in land certificates ensures that the land registration process is conducted fairly, accurately, and openly. Third, land certificates serve as a perfect means of proof in the legal system, providing legal protection for landowners and preventing ownership disputes.